Spillover Effects of Medicare Advantage on Traditional Medicare Beneficiaries With Prostate Cancer - Arnav Srivastava; Samuel R. Kaufman; Xiu Liu; Avinash Maganty; Addison Shay; Mary Oerline; Christopher Dall; Kassem S. Faraj; Paula Guro; Dawson Hill; Thuy Nguyen; Lindsey A. Herrel; et al. (Cancer Medicine)
ABSTRACT Introduction Medicare Advantage (MA) managed care plans, now chosen by 51% of Medicare beneficiaries, are incentivized to constrain healthcare spending and utilization, a shift in financial incentives compared to Traditional Medicare's fee‐for‐service payment model. Beyond its primary beneficiaries, MA's mechanisms to constrain utilization may impact Traditional Medicare beneficiaries with prostate cancer through “spillover” effects on physician behavior. Methods From a 20% sample of Medicare claims, we identified patients diagnosed with prostate cancer from 2016 to 2019. We calculated MA penetration [MA beneficiaries/(Traditional Medicare and MA beneficiaries)] at the practice‐level. We assessed the relationship between practice‐level MA penetration and two measures of quality—potential overtreatment (i.e., treatment among those with > 75% noncancer mortality within 10 years of diagnosis) and confirmatory testing (repeat prostate biopsy, MRI, or genomic test)—using a multilevel logistic regression. We also assessed two measures of utilization, price standardized spending (i.e., global utilization) and overall treatment. Results We identified 41,092 patients. Median practice‐level MA penetration was 33% (IQR 23%–43%). Increasing practice‐level MA penetration was associated with increased odds of overall treatment among all Traditional Medicare beneficiaries (adjusted OR 1.03 (95% CI 1.01–1.05), p = 0.01, per 10% increase in MA penetration). However, MA penetration was not associated with our quality measures, potential overtreatment and confirmatory testing, or price‐standardized spending. Conclusions MA penetration at the urology practice‐level varies considerably. In men with prostate cancer, greater practice‐level MA penetration was associated with increased odds of treatment, but not overall utilization—even where it might influence quality.